Ambivalensi Kebijakan Pertambangan Rakyat dalam Perspektif Etika Islam dan Maqasid al-Syari‘ah - Gusti Andrie Asriansyah; Dwi Surya Atmaja (Kartika: Jurnal Studi Keislaman, 2026)
This study examines the ambivalence of artisanal mining policies in Landak Regency from the perspective of Islamic ethics and maqasid al-syari'ah. Using a qualitative approach with case studies in Meranti and Kuala Behe sub-districts, this research analyzes the gap between state regulations (2025 Minerba Law), the meaning of rizq (sustenance) among Muslim miners, local philanthropic practices (HUMUS), and ecological awareness. The findings indicate that: (1) miners interpret rizq ambivalently as Allah's blessing requiring effort, yet facing legal dilemmas and ecological impacts; (2) HUMUS functions as a mechanism for moral legitimacy and social solidarity, but potentially becomes spiritual compensation for environmental damage; (3) ecological awareness exists in an ambivalent position between moral recognition and structural inability to change; (4) the 2025 Minerba Law places artisanal miners in a marginal position, though the People's Mining Area (WPR) policy offers a middle ground. From the maqasid al-syari'ah perspective, conflicts between hifz al-mal (protection of wealth), hifz al-nafs (protection of life), and hifz al-bi'ah (protection of environment) require structural solutions based on ecological justice and Islamic economics, particularly through a musyarakah-based mining cooperative model